2014
DOI: 10.1111/poms.12242
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Contribution of Workers' Health and Psychosocial Work‐Environment on Production Efficiency

Abstract: I ncreasingly many firms have started to implement programs intended to improve the workers' health and the psychosocial work-environment, as well as other attributes of labor quality. Motivated by the need for evaluating to what extent the programs affect a firm's productivity performance, this study discusses a model for analyzing the contribution of labor quality attributes toward firm productivity. To assess the contribution from the labor quality attributes, we model firm productivity as the outcome of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 60 publications
(96 reference statements)
0
21
0
Order By: Relevance
“…Productivity analyses are an often-studied area within the field of production and operational management. Previous studies have examined workers' productivity from the viewpoint of job-related issues [10][11][12][13], technology [15,18], worker demographics and socioeconomic features [7,19,22,31], and worker health conditions [34][35][36][42][43][44][45]55,56]. Although previous research has explored several factors contributing to workers' productivity, few studies have examined the link between workers' on-job emotional states and productivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Productivity analyses are an often-studied area within the field of production and operational management. Previous studies have examined workers' productivity from the viewpoint of job-related issues [10][11][12][13], technology [15,18], worker demographics and socioeconomic features [7,19,22,31], and worker health conditions [34][35][36][42][43][44][45]55,56]. Although previous research has explored several factors contributing to workers' productivity, few studies have examined the link between workers' on-job emotional states and productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also emphasized how an employee's health and wellbeing impact productivity. Neumann and Dul [42], as well as Ødegaard and Roos [43], found that healthier employees are more productive. Gubler, Larkin, and Pierce [44] provided evidence that implementing a corporate wellness program improved employee productivity.…”
Section: Introductionmentioning
confidence: 95%
“…For example, Pericoli et al . () use their index to explain the impact of social capital on consumption insurance and income volatility, while Ødegaard and Roos () use predicted values of latent labour quality in a DEA study explaining the productive efficiency of large firms in Sweden.…”
Section: Empirical Strategymentioning
confidence: 99%
“…The remaining 4 studies (4%) all used ad hoc approaches that (41, 45-48, 51, 56-58, 60, 62, 64, 66, 68, 70, 72-75, 79, 81, 83, 84, 87-90, 92, 93, 95, 97, 98, 100-102, 105, 107-110, 113, 117-125) North-America 34 (39, 40, 43, 44, 50, 52-55, 59, 61, 63, 65, 69, 71, 76, 80, 82, 85, 86, 91, 94, 96, 99, 103, 106, 111, 112, 114-116, 126- (39, 41, 42, 44, 45,49,50,(52)(53)(54)(55)59,60,67,68,70,71,76,77,82,87,95,115, 128) Inferred: 19 (40, 43, 46,57,61,63,65,80,86,91,92,94,96,103,111,116,(125)(126)(127)56,62,64,66,69,72,73,75,78,79,81,(83)(84)(85)…”
Section: Productivity Estimation Methodsmentioning
confidence: 99%
“…Only 5 (50,55,59,76,92) of the 90 studies did not include a measure of lost-time (absenteeism or presenteeism). This is because, in addition to studies with a primary or secondary method that used lost-time (productivity in natural units, HCA, or FCA), several of the ad hoc and output-based methods measured absenteeism or presenteeism.…”
Section: Measuring Time Lossmentioning
confidence: 99%